If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -27 = -7(3b + -8) Reorder the terms: -27 = -7(-8 + 3b) -27 = (-8 * -7 + 3b * -7) -27 = (56 + -21b) Solving -27 = 56 + -21b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '21b' to each side of the equation. -27 + 21b = 56 + -21b + 21b Combine like terms: -21b + 21b = 0 -27 + 21b = 56 + 0 -27 + 21b = 56 Add '27' to each side of the equation. -27 + 27 + 21b = 56 + 27 Combine like terms: -27 + 27 = 0 0 + 21b = 56 + 27 21b = 56 + 27 Combine like terms: 56 + 27 = 83 21b = 83 Divide each side by '21'. b = 3.952380952 Simplifying b = 3.952380952
| 2h-4x=13 | | M+4m=-15 | | 2x^2+x=180 | | E=8b+12nforb | | -23=2n-7n | | 4x-2h=13 | | -18x-24=-9x+3 | | 3(5+7p)=120 | | (6x^3-4)+(2x^3+9)= | | -2(9d-8)=34+6d | | -b-4+3b=3+b | | X+17=3x-23 | | 5x+2y^3+xy^2=0 | | 8x+11-6x=5(x+7) | | 5x+2x-8=13 | | 4y-13=23# | | 48t-33=51t-69 | | -3(10)+9=-21 | | -98=2(-7+7x) | | 8(6-7y)=26 | | -3-6n=-3(1+4n)+6n | | 4x+24=8x-12 | | 1.2d-6= | | 18=28+4(-5) | | 4x+7x+8+7x+2=172 | | -5n-5(-8n+3)=13+7n | | -7-4x=2x-7(1-7x) | | 2(5-x)-5x=3-(2+4) | | 5(2)5x=15 | | -5m=4-6m | | -5v-4+7v=-25 | | x+9+12x+7=159 |